Pengaruh Service Quality, Preceived Value dan Brand Image Terhadap Loyalitas Pelanggan Trans Lulo Kota Kendari - Rahman, Muljibir (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2021)
This study aims to analyze the relationship between the variables of Service Quality, Preceived Value, Brand Image and Consumer Loyalty through a case study on Trans Lulo Bus passengers in Kendari City. The sampling technique used in this research is to use the purposive sampling method. The sample used in this study is the Kendari city community who have used the Kendari City Translulo transportation service. The number of samples in this study were 94 people. The analytical method used in this study uses Structural Equation Modeling (SEM) using the SMART PLS 3.0 program. The results of this study indicate that Brand Image and Service Quality have a positive and significant effect on customer loyalty, then perceived value has a positive and significant effect on brand image. While perceived value does not have a positive and significant effect on Customer Loyalty, then Service Quality has no significant effect on Brand Image